Analisis Tren Belanja Pertahanan dalam Memberikan Dampak terhadap Kemandirian Industri Pertahanan - Mohadib, Mohadib; Andriansyah, Andriansyah (Jurnal Disrupsi Bisnis, 2024)
This research aims to analyze defense spending trends and their impact on the self-sufficiency of the defense industry in Indonesia. The article adopts a qualitative approach based on document analysis or desk research. The results of the analysis indicate that Indonesia's defense spending trends, influenced by positive economic growth, security threats, and the government's commitment to defense industry self-sufficiency, have fluctuated in the period 2019-2024. Despite decreases in 2023 and 2024, defense budgets remain significant, reflecting the government's commitment to national defense. However, defense spending trends have not significantly impacted the self-sufficiency of the defense industry. Criticisms involve insufficient technology transfer, limited orders, and dependence on imported defense equipment. Achieving self-sufficiency requires political will and policy changes for long-term development. Full government support, both in budgetary allocations and policies, is crucial to attaining the desired self-sufficiency and addressing global dynamics.